Caracterização nutricional do Eucalyptus benthamii Maiden & Cambage em área de produção de sementes - Souza, Huan Pablo de (2015)
Eucalyptus is the most planted forest genus in Brazil and worldwide. The eucalyptus plantations are established in various environments, and in the state of Rio Grande do Sul, new plantations are being established in the Pampa biome region. Therefore, there is need to use appropriate and correct genetic material nutritional management of stands. This study aimed to characterize nutritionally one Seed Production Area (APS) Eucalyptus benthamii, to six years in the city of São Francisco de Assis - RS, on the farm Estância das Oliveiras, owned by Stora Enso Florestal RS company. For the study, nine trees were harvested in three diameter classes, where samples of biomass were obtained above and below ground (leaves, branches, wood, bark, fruits and root) with subsequent determination of the dry mass and the concentration of macro and micronutrients. The total biomass in Seed Production Area was 47,59 Mg ha-1, with the following percentage of biomass: 62,14% in the wood, 10,19% in the branches, 8,26% in the bark, the leaves has 6,25%, 0,05% in the fruits and 13.11% in the roots. The stock of elements in the total biomass accumulation showed the following order of macronutrients: N > K > Ca > Mg > P > S and micronutrients to the order of distribution was as follows: Fe > Mn > Zn > B > Cu. The macronutrient concentrations in the biomass followed the sequence: wood > roots > leaves > branches > bark > fruit. For micronutrient concentrations follow the order: root > wood > branches > leaves > bark > fruit. The export of nutrients by the intensity of harvest of biomass components had the following distribution trend in the collection scenario 1 (30% removal leaves, twigs + 30% + 100% fruit): Mn> N> Cu> K> Mg> S> B> Ca> P> Zn> Fe Considering the scenario 2 (50% removal leaves, twigs + 50% + 100% fruit) harvesting the export of nutrients had the following distribution: Mn > N> Cu> K> Ca> Mg> S> B> P> Zn> Fe. For the scenario of harvest 3 (removal of 100% + 100% leaves and branches all fruit) export of nutrients presented following distribution: Mn> N> Cu> B> Mg> K> Ca> S> P> Zn> Fe